Effects of Multiple Sedentary Days on Metabolic Risk Factors in Free-Living Conditions: Lessons Learned and Future Recommendations - Altenburg, Teatske M.; Rotteveel, Joost; Serné, Erik H.; Chinapaw, Mai J. M. (Frontiers in Physiology, 2016)
BACKGROUND Recent experimental studies in adults have demonstrated that interruptions to prolonged sitting have beneficial effects on metabolic risk factors in adults, compared to prolonged sitting. We explored the hypothesis that multiple consecutive days of predominantly prolonged sedentary time may have an unfavorable effect on the postprandial response of C-peptide, glucose and triglycerides in free-living healthy young men. METHODS In this explorative pilot study, healthy young men (n=7; 18-23yrs) consumed standardized mixed meals at 1 and 5 hours during two experimental laboratory-sitting days, with six days of predominantly prolonged sedentary time in between. Serum and plasma samples were obtained hourly from 0 to 8 hours for measurement of glucose, C-peptide and triglycerides. Participant’s sedentary time was monitored using an accelerometer during the prolonged sedentary days as well as during six normal days prior to the first laboratory day. Differences in postprandial levels were assessed using generalized estimating equations analysis. Due to the explorative nature of this study and the small sample size, p-value was set at <0.10. RESULTS Overall, when expressed as % of wear time, sedentary time was 5% higher during the six prolonged sedentary days, which was not significantly different compared to the six normal days (n=4). Following six prolonged sedentary days, postprandial levels of C-peptide were significantly higher than at baseline (B=0.11; 90%CI=[0.002; 0.22]; n=7). Postprandial levels of glucose and triglycerides were not significantly different between the two laboratory days. CONCLUSIONS Due to the relatively high sedentary time at baseline, participants were unable to increase their sedentary time substantially. Nevertheless, postprandial C-peptide levels were slightly higher after six prolonged sedentary days than after six normal days.